SLANG DALAM LAGU BLACK EYED PEAS - Adolof, Kheren Kezia (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
This research design entitled ?Slangs in the Songs of Black Eyed Peas? is an attempt to identify the slangs in the songs of Black Eyed Peas, analyze and describe their forms and meanings. The theory  used in this research is by Bloomfield and this research applies a despcriptive methokd. Theoretically, this research will give a contribution to linguistic study especially on Sociolinguistics field more specifically on slangs found in the songs ofBlack Eyed Peas and also provide with rich information about slang.Practically, this study can help the students or the readers and the writer herself in understanding slang in terms of form and meaning in songs. The result show that the forms of slangs in the songs are abbreviation, facetious, misprounuciation, shortened forms, interjection, figurative expression, and nick name (calling person). There are some forms that cannot be found in the songs, they are interjection, and figurative expression form.   Keywords: slang, Songs of Black Eyed Peas, Bloomfield?s theory